2009
DOI: 10.1097/ico.0b013e318199f8d7
|View full text |Cite
|
Sign up to set email alerts
|

Descemet's Stripping Automated Endothelial Keratoplasty (DSAEK) Using Corneal Donor Tissue Not Acceptable for Use in Penetrating Keratoplasty as a Result of Anterior Stromal Scars, Pterygia, and Previous Corneal Refractive Surgical Procedures

Abstract: Postoperative results of DSAEK using donor tissue excluded from use in penetrating keratoplasty as a result of stromal flaws are equivalent to results using standard donor tissue. Central corneal thickness measurements should be performed before cutting to avoid tissue perforation. The use of ASF tissue for DSAEK will expand the cornea donor pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…They compared the aggregate ASF donor tissue DSAEK results with a control DSAEK group and found no difference in visual acuity, topography, astigmatism, pachymetry, or ECD. Our reported visual acuity (20/25 to 20/40, excluding case 5) and ECD (loss of 33.1% in our series and 32% in the serious of Phillips et al 4 ) are very similar to the ASF donor tissue outcomes reported by Phillips et al 4 We found no difference in smoothness of the cap-cut surface in the number of frayed posterior collagen fibers in LASIK versus non-LASIK donor caps centrally and peripherally. The similarity in best spectacle-corrected visual acuity outcomes with the use of LASIK and PRK donor tissue as compared with normal donor tissue is likely a result of the smoothness of the prepared interface in the postrefractive surgery tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They compared the aggregate ASF donor tissue DSAEK results with a control DSAEK group and found no difference in visual acuity, topography, astigmatism, pachymetry, or ECD. Our reported visual acuity (20/25 to 20/40, excluding case 5) and ECD (loss of 33.1% in our series and 32% in the serious of Phillips et al 4 ) are very similar to the ASF donor tissue outcomes reported by Phillips et al 4 We found no difference in smoothness of the cap-cut surface in the number of frayed posterior collagen fibers in LASIK versus non-LASIK donor caps centrally and peripherally. The similarity in best spectacle-corrected visual acuity outcomes with the use of LASIK and PRK donor tissue as compared with normal donor tissue is likely a result of the smoothness of the prepared interface in the postrefractive surgery tissues.…”
Section: Discussionsupporting
confidence: 92%
“…3,4 We report the first case of DSAEK using a PRK donor cornea and 6 cases of DSAEK using LASIK donor cornea along with histopathology of 3 LASIK donor caps from DSAEK microkeratome preparation.…”
mentioning
confidence: 98%
“…6 months there was no statistically significant difference in the best-corrected acuity, endothelial cell count, and topographic measurements of the surface regularity index and surface asymmetry index between cases and controls [11]. Khalifa et al reported their analysis of preparation of two corneal lenticules with prior RK, prepared with a microkeratome.…”
Section: Endothelial Transplants With Anterior Stromal Flawed Donorsmentioning
confidence: 97%
“…This potential is bolstered by the Eye Bank Association of America's (EBAA) 2005 decision to expand the criteria for acceptable tissue: [102] corneas that had been deemed unsuitable for PK because of anterior scarring, central pterygia, or corneal refractive surgeries such as radial keratotomy (RK) are now being effectively used in EK procedures [104,105]. It is therefore increasingly important that each donor cornea is evaluated both accurately and efficiently in order to make the best use of all available tissue.…”
Section: Optical Coherence Tomography In Eye Bankingmentioning
confidence: 99%